Teams and Tournaments in Relational Contracts - Ola Kvaløy; Trond Olsen (Center for Economic Studies and ifo Institute (CESifo), 2014)
We analyze relational contracts for a set of agents when either (a) only aggregate output or (b) individual outputs are observable. A team incentive scheme, where each agent is paid a bonus for aggregate output above a threshold, is optimal in case (a). The team's efficiency may increase considerably with size if outputs are negatively correlated. Under (b) a tournament scheme with a threshold is optimal, where the threshold, for correlated outputs, depends on an agent's relative performance. The two cases reveal that it may be optimal to organize production as a team where only aggregate output is observable.
Keywords: D89; J29; L23; M52; 330; relational contracts; teams; tournaments